TRANSLATION THEORY: CHALLENGES IN TRANSLATING CULTURAL CONTEXTS - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article examines the challenges of translating cultural contexts, emphasizing the complexities inherent in conveying meaning, tone, style, and sociocultural nuances across languages. It explores theoretical frameworks in translation studies, including dynamic equivalence, foreignization, and domestication, and highlights the difficulties posed by idioms, proverbs, historical references, humor, and stylistic features. The study also addresses pragmatic, syntactic, and lexical differences between languages and the ethical responsibilities of translators as cultural mediators. Additionally, the article considers the impact of technological developments, such as machine translation and AI, on translating culturally rich texts. It concludes that successful translation requires a combination of linguistic skill, cultural competence, and ethical awareness to achieve effective cross-cultural communication and preserve the integrity of source texts.